Morphinan Alkaloids from the Leaves of Alphonsea cylindrica and Their Antibacterial Properties - Cho, Kin-Hau; Tan, Siow-Ping; Tan, Hui-Yin; Liew, Sook Yee; Nafiah, Mohd Azlan (Planta Medica, 2022)
A phytochemical study has been carried out on CH2Cl2 extract of Alphonsea cylindrica leaves, resulting in the isolation of three new morphinan alkaloids. They are kinomenine (1), N-methylkinomenine (2), and hydroxymethylkinomenine (3). The structures of these compounds were elucidated by extensive spectroscopic analysis (1D and 2D NMR, IR, UV, HRESIMS) and comparison with the data reported in literature for similar alkaloids. Kinomenine (1) and N-methylkinomenine (2) showed weak inhibition against S. aureus (MIC values of 1 and 2 = 500 µg/mL; pIC50 values in 95% C. I. of: 1 = 2.9 to 3.0; 2 = 2.9 to 3.1), while kinomenine (1) also showed weak inhibition against E. coli (MIC values of 1 = 500 µg/mL; pIC50 value in 95% C. I. of: 1 = 2.9) by broth microdilution method. The results obtained can be used as future referencefor the discovery of morphinans and the potential of A. cylindrica as an antibacterial source.
Keywords: Annonaceae; Alphonsea cylindrica; morphinan alkaloids; kinomenine; antibacterial properties